Implementasi E-commerce Shopee Pada Keberhasilan Pemasaran Usaha Mamask - Rahmawati, Alfina; Izazi, Zsa Zsa (PUTRA JAWA PUBLISHER, 2024)
The objectives of this study are to (1) explain the supporting factors that influence the success of entrepreneurial marketing through Shopee e-commerce business on Mamask business, (2) explain the factors that hinder the success of entrepreneurial marketing through Shopee e-commerce business on Mamask business, and (3) explain the approach to entrepreneurial marketing through Shopee e-commerce business. This study conducted qualitative research with a case study design. The data for this study was obtained through interviews with resource persons. This study used observation, interviews, and documentation to collect data. There are three components that must be considered when using Shopee e-commerce in marketing: marketing strategies, factors inhibiting marketing success, and factors driving the success of Shopee e-commerce marketing. The results of this study show that (1) by maximizing the factors supporting the success of Shopee e-commerce marketing.